Generation and Characterization of an Atmospheric-Pressure Plasma Jet (APPJ) and Its Application in the Surface Modification of Polyethylene Terephthalate. (11th February 2020) - Baniya, Hom Bahadur; Shrestha, Rajendra; Guragain, Rajesh Prakash; Kshetri, Mohan Bahadur; Pandey, Bishnu Prasad; Subedi, Deepak Prasad
Abstract : An atmospheric-pressure plasma jet (APPJ) has a lot of applications in recent years such as in material processing, surface modification, biomedical material processing, and thin film deposition. APPJ has been generated by a high-voltage power supply (0-20 kV) at an operating frequency of 27 kHz. This paper reports the generation and characterization of APPJ in argon environment and its application in the surface modification of polyethylene terephthalate (PET). The plasma jet has been characterized by electrical and optical methods. In order to characterize the plasma jet, electron density and electron temperature have been determined. The surface roughness of the untreated and plasma-treated PET samples was characterized by contact angle measurement, surface energy analysis, Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), and atomic force microscopy (AFM).